Education Quality Management Based on Islamic Boarding School - Risa Diningrum; Eni Fariyatul Fahyuni; Renny Oktafia (Proceedings of The ICECRS, 2020)
Islamic boarding school is the oldest educational institution by the nation that participated in creating literate society. In the midst of this globalization era, Islamic boarding schools maintain both classical and modern education and teaching systems. In educational institutions need to pay attention to the quality management of education in order to improve and develop educational institutions for the future. The reality that we get in guaranteeing the quality of education in Islamic boarding schools is that there are many obstacles that must be resolved. With this the author intends to examine several management systems or quality management based on Islamic boarding schools. This study used qualitative research methods. This research is specifically directed towards descriptive qualitative research design. Trying to solve the problem based on the data concerned with the concept of quality management based on Islamic boarding school. The concept that has been prepared in the management of education quality in Islamic boarding schools is oriented to improving the quality of education by referring to the values ​​of Islamic boarding schools / Islamic society that have been entrenched among Indonesian people, by using tools, techniques and philosophies to create quality education in order to achieve educational goals.